2017
DOI: 10.1007/s00277-017-3057-z
|View full text |Cite
|
Sign up to set email alerts
|

Soluble form of transferrin receptor-1 level is associated with the age at first diagnosis and the risk of therapeutic intervention and iron overloading in patients with non-transfusion-dependent thalassemia

Abstract: We retrospectively evaluated the relationship between serum transferrin receptor-1 (sTfR1) and some fundamental events in the life and the management (the age at diagnosis, the age at the first red blood cells transfusion, the age at splenectomy, and the overall need of chelation therapy) of 111 patients with non-transfusion-dependent thalassemia (NTDT) subdivided in four genetic entities: patients with homozygous or compound heterozygous state for β-thalassemia, patients with triplicated α genotype associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Interestingly, these patients had lower blood consumption with respect to patients with TM enrolled in the MIOT project [mean (SD) 102·02 (74·08) vs. 176·75 (51·91) ml/kg/year; P < 0·0001), thus suggesting the permanence of a residual higher erythropoietic drive. Following the start of BTs, we found not only the down‐regulation of all erythropoietic and/or haemolysis indices, 26‐28 but also a drop in platelets and white blood cell count, indicating a complex and pleiotropic effect on bone marrow function. On the other hand, renal function was not affected, likely because most patients had normal creatinine and were not hyperfiltrating at baseline.…”
Section: Discussionmentioning
confidence: 81%
“…Interestingly, these patients had lower blood consumption with respect to patients with TM enrolled in the MIOT project [mean (SD) 102·02 (74·08) vs. 176·75 (51·91) ml/kg/year; P < 0·0001), thus suggesting the permanence of a residual higher erythropoietic drive. Following the start of BTs, we found not only the down‐regulation of all erythropoietic and/or haemolysis indices, 26‐28 but also a drop in platelets and white blood cell count, indicating a complex and pleiotropic effect on bone marrow function. On the other hand, renal function was not affected, likely because most patients had normal creatinine and were not hyperfiltrating at baseline.…”
Section: Discussionmentioning
confidence: 81%
“…Median age was similar in the two groups (p > 0.05). Hemoglobin levels were significantly lower (p < 0.01) in females, while ineffective erythropoiesis and expanded erythropoiesis biomarkers, such as soluble transferrin receptor (sTfR) [7] and nucleated red blood cells (NRBC), were comparable. There was no significant difference for other laboratory parameters, except for serum creatinine and uric acid levels, which were lower in females, according to data reported in the general population.…”
Section: Resultsmentioning
confidence: 97%
“…Despite the availability of recent guidelines from the Thalassaemia International Federation (TIF), the proper management of patients with non‐transfusion dependent thalassaemia (NTDT) is still under debate (Taher et al , ; Ricchi et al , ). We previously showed that the soluble transferrin receptor‐1 (sTfR1) level, was a reliable biomarker for predicting the risk of extramedullary haematopoiesis (EMH) and for scoring disease severity (Ricchi et al , , , , , ). The purpose of this study is to further validate its use, based on a longer term prospective assessment among our NTDT patients.…”
Section: Baseline Characteristics Of the Patientsmentioning
confidence: 99%
“…Of the 16 and 12 patients who underwent BT and HC treatment, 12 and 11 had the combination of a β defect plus a β chain variant, respectively ( P < 0·001; Table ). Serum levels of sTfR1 were determined at a median of once a year and at least 2 months from the previous transfusion, as previously described (Ricchi et al , ). Intra‐individual variability of sTfR1 was assessed in all groups, evaluating the intra‐person over time percentage coefficient of variation (% CV).…”
Section: Baseline Characteristics Of the Patientsmentioning
confidence: 99%